Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Simply the expression 3(2y - 8) - 2y(5-y)

Sagot :

Answer:

-4y - 24 + 2y²

Step-by-step explanation:

1. Simplify the distributive properties

⇒ 3(2y - 8) - 2y(5 - y)

⇒ 6y - 24 - 10y + 2y²

2. Combine like terms

⇒ 6y - 24 - 10y + 2y²

⇒ y(6 - 10) - 24 + 2y²

3. Simplify the expression

⇒ y(6 - 10) - 24 + 2y²

-4y - 24 + 2y²